2022
DOI: 10.3390/nu14071356
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Analgesic Effects of Schisandra chinensis Leaf Extracts and Monosodium Iodoacetate-Induced Osteoarthritis in Rats and Acetic Acid-Induced Writhing in Mice

Abstract: In this study, we aimed to determine the anti-inflammatory and antinociceptive activities of Schisandra chinensis leaf extracts (SCLE) in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages, an acetic acid-induced mouse model of writhing, and a monosodium iodoacetate (MIA)-induced rat model of osteoarthritis (OA). In LPS-stimulated RAW264.7 cells, a 100 µg/mL dose of SCLE significantly reduced the production of nitric oxide (NO), interleukin-1β (IL-1β), tumour necrosis factor-alpha (TNF-α), interleukin-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
2
8
0
1
Order By: Relevance
“…In addition, several studies have shown that Schisandrin A and B can inhibit cartilage degradation by inhibiting the NF‐κB and MAPK signalling pathway 37,38 . Other studies have shown that the Schisandra leaf extract blocks inflammatory effects and could be useful for treating OA 22,23 . In the present study, oral administration of the Schisandra extract protected against cartilage breakdown in a DMM mouse model of OA.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In addition, several studies have shown that Schisandrin A and B can inhibit cartilage degradation by inhibiting the NF‐κB and MAPK signalling pathway 37,38 . Other studies have shown that the Schisandra leaf extract blocks inflammatory effects and could be useful for treating OA 22,23 . In the present study, oral administration of the Schisandra extract protected against cartilage breakdown in a DMM mouse model of OA.…”
Section: Discussionsupporting
confidence: 61%
“…Recent studies have shown that the extracts of Schisandra possess biological activities, including anticancer, antioxidant, neuroprotective, hepatoprotective and anti‐inflammatory activities 21 . In addition, studies have reported that the Schisandra leaf extract relieves pain and inflammation in a rat model of OA 22,23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of NF-κB could induce the expression of major pro-inflammatory mediators of COX-2, which may result in oxidative stress . As shown in Figure C, the COX-2 expression was extremely low in the control group, and when cells were stimulated by LPS, the expression level in inflammatory cells can be increased to tens of times as compared to the control group.…”
Section: Results and Discussionmentioning
confidence: 94%
“…As a medicinal and food product, schisandra is mostly used in the eld of medicine. In some recent studies, it has been found that lignans, the active ingredients in a variety of schisandra seeds, have superior neuroprotective, hepatic and renal cellular and in ammation-relieving effects [14][15][16][17], while polysaccharides have strong antioxidant, immunomodulatory, hypoglycaemic and lipid-lowering properties [18][19][20][21][22]. Multiple effects give Schisandra a wide range of applications.To our best knowledge, few researches concerning the potential anti-fatigue property of Schisandra chinensis were published yet.…”
Section: Introductionmentioning
confidence: 99%